Synthesis and Characterization of Ibuprofen Delivery System Based on β-cyclodextrin/Itaconic Acid Copolymer - Haroun, Ahmed; Osman, Ali; Ahmed, Sayed; Elghandour, Ahmed H. (Trends in Sciences, 2022)
This study aims at preparation and characterization of drug delivery system based on grafted beta-cyclodextrin (β-CD) with itaconic acid (IA) using free-radical copolymerization technique, in the presence of N, N’-methylene bisacrylamide (BIS) and ammonium persulphate (APS) as a crosslinker and an initiator, respectively. The obtained copolymer (CD-PIA) was characterized using Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), X-ray diffraction patterns (XRD), transmission and scanning electron microscopes (TEM and SEM). Ibuprofen (IBU), as an anti-inflammatory drug model, was loaded during the preparation. The kinetic of the copolymerization was investigated in terms of grafting yield (GY %), grafting efficiency (GE %) and monomer conversion (%). Moreover, in vitro IBU release and kinetic of released using the different mathematical models (0-order, first-order and Higushi) were carried out in simulated gastric and intestinal fluids (SGF and SIF at pH 1.2 and 7.4, respectively) at 37 °. The results proved the successful preparation of the target copolymer with irregular spherical-like shape and particle size around 14 - 27.7 nm. After IBU loading, the copolymer exhibited thermal stability with crystalline nature. Also, the study showed that the synthesized copolymer, especially which high IA content is controlled the release of IBU after 4 h. Besides, it could be used as a potential IBU delivery system with sustained-release followed the first-order kinetic over 24 h. HIGHLIGHTS The nanogels drug carriers used for nonsteroidal anti-inflammatory drugs to overcome the unfavorable release in the stomach due to unforeseen pH alterations The polymeric grafted β-CD derivatives using IA represent a unique class of the host materials with tunable inclusion properties and high affinity for Ibuprofen release In vitro kinetic of IBU released showed the best fit with first-order model GRAPHICAL ABSTRACT